Bioelectrics - Akiyama, Hidenori, 1951-; Heller, Richard, 1954- (Springer, 2017)
This book focuses on bioelectrics, a new multidisciplinary field encompassing engineering and biology with applications to the medical, environmental, food, energy, and biotechnological fields. At present, 15 universities and institutes in Japan, the USA and the EU comprise the International Consortium of Bioelectrics, intended to advance this novel and important research field. This book will serve as an introductory resource for young scientists and also as a textbook for use by both undergraduate and graduate students - the world's first such work solely devoted to bioelectrics.
Keywords: Electrophysiology.; Bioelectronics.; Bioelectrochemistry.; elektronické knihy; electronic books